Family Violence Against Working Women During Covid - 19 and its Relationship with their Psychological Burnout in Amman - محمود صالح بنات, سهيلة; خالد سليمان الجمعاني , أمل (Journal of College of Education, 2022)
This study aimed to investigate the domestic violence against working women during the covid-19 pandemic and its relation to their psychological burnout in the capital, Amman city. The study population consisted of (400) female employees from the Greater Amman Municipality. To achieve the objectives of the study, we used the two study tools were they Domestic Violence Scale, consisting of (33) items, and Maslash Scale of Psychological Burnout, consisting of (21) items, and they were applied to the study sample after extracting the validity and reliability coefficients for them, and the descriptive correlative approach was used in this study. The results indicated that the level of domestic violence against working women during the Corona pandemic in the capital Amman is low, and that the level of psychological burnout among working women during the Corona pandemic was medium , and that there were no statistically significant differences in the level of domestic violence against working women during the Corona pandemic in the capital Amman city according to age and the occupational level. and there were statistically significant differences in the level of violence against working women during the Corona pandemic in the capital Amman according to the difference in social status, and differences in the averages and standard deviations of the level of psychological burnout among working women during the Corona pandemic in the capital Amman according to different social status, age and occupational level And statistically significant positive relation at the significance level (α= 0.05) between domestic violence and the level of psychological burnout among working women during the Corona pandemic. Based on the results of the study, the researcher recommends conducting more surveys, qualitative and experimental studies related to the level of domestic violence and psychological burnout in different regions and different groups.
Keywords: Family Violence; psychological burnout; Working Women; Covid - 19